Could least developed countries (LDCs) and other developing countries which have not been able to establish legal framework for the application of trade remedy measures make a beginning by establishing mechanism for the application of safeguard measures only? - Rege, Vinod (2013)
Notes that in pursuing liberal and open trade policies, countries may have to use trade remedy measures such as anti-dumping countervailing or safeguard measures in cases where their domestic agricultural producers or manufacturing industries are hurt or injured by imports. Suggests that the least developed and other developing countries which have not been able to establish legal and institutional framework for applying all the three trade remedy measures should be permitted to apply only safeguard measures, which from the administrative point of view would require only modest staff, by adopting an Understanding.